Redesign Sistem Karya Akhir Universitas Pendidikan Ganesha menggunakan Pendekatan Design Thinking - Putra, Decky Pratama; Arthana, I Ketut Resika; Putra, I Nyoman Tri Anindia (Fakultas Sains Dan Teknologi, Universitas Raden Rahmat Malang, 2025)
The Final Project System at Undiksha plays an essential role in supporting academic administration; however, initial findings reveal issues related to navigation flow, interface clarity, and system feedback that reduce usability. This study analyzes the system’s usability and proposes a redesign using the Design Thinking approach through empathize, define, ideate, prototype, and test stages. The pre-test evaluation indicated an effectiveness and efficiency score of 79.99% and a QUIS satisfaction score of 3.70. After implementing improvements in navigation, progress visualization, layout consistency, and responsive feedback, post-test results increased effectiveness to 91.67% and efficiency to 91.67%, while the satisfaction score rose to 4.74, representing a 28.1% improvement. These results demonstrate that the proposed redesign significantly reduces user errors, accelerates task completion, and enhances overall interaction quality. The study contributes empirical evidence supporting iterative interface improvements to optimize academic web services.